Meropenem-Vaborbactam for the Treatment of Post-Neurosurgical Meningitis Caused by KPC Producer Klebsiella Pneumoniae: A Case Report and Review of the Literature - Leonardo Francesco Rezzonico; Francesco Peracchi; Marta Vecchi; Gabriele Bassi; Marco Merli; Nicholas Brian Bana; Giovanna Travi; Fulvio Crippa; Massimo Puoti (MDPI AG, 2024)
Meningitis and ventriculitis, due to carbapenem-resistant Enterobacterales, are frequently associated with significant morbidity and mortality. In the case of multi-drug-resistant pathogens, it is necessary to consider the limited susceptibility profile as well as the penetration of the antimicrobials into the brain. Limited data are available regarding the treatment of central nervous system infections caused by carbapenem-resistant Enterobacterales. We report a study of a patient treated with meropenem-vaborbactam in the case of post-neurosurgical meningitis due to carbapenemase-producing Klebsiella pneumoniae (CPKP).